THE EFFECTS OF POVERTY ON THE HUMAN PSYCHE REFLECTED IN RUPERT BROOKE’S LITHUANIA: A PSYCHOANALYTIC STUDY - Sumarsono, Irwan (Lire Journal (Journal of Linguistics and Literature), 2023)
This study analyzes the psychological effects of poverty on individuals using Rupert Brooke's play, "Lithuania," as a case study. The motivations behind the characters' murders are explored through a descriptive qualitative methodology that collects data from various sources, including literature and psychology. Applying Freud's psychoanalytic theory, the study highlights the profound impact of poverty on the characters' psyche, particularly their inability to control their id-driven desire for wealth. The findings emphasize the importance of understanding the psychological effects of poverty on people's behavior and decision-making, as well as the value of literature in comprehending human nature. The study sheds light on how societal attitudes towards wealth and poverty can impact our sense of morality and ethical decision-making. This investigation contributes to the growing body of research on the intersection between literature and psychology and has practical implications for policymakers and social workers dealing with poverty-related issues.